2024
DOI: 10.1039/d3sc06357g
|View full text |Cite
|
Sign up to set email alerts
|

Redox-mediated electrochemiluminescence enhancement for bead-based immunoassay

Alessandro Fracassa,
Claudio Ignazio Santo,
Emily Kerr
et al.

Abstract: Redox mediated mechanism in electrochemiluminescence (ECL) beads-based assay: the influence of Ir(iii) redox mediators increases the ECL signal up to 107%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…However, recent investigations of homogeneous oxidation of TPrA by a freely diffusing Ir complex demonstrated that this strategy can increase the ECL signal from a microbeads immunoassay, i.e., heterogeneous system by a “redox mediated” pathway (Fig. 6 ) [ 55 , 56 ]. The Ir(III) complex oxidized at the electrode to produce Ir(II) can oxidize the TPrA, which result in the formation of TPrA • , and in addition, it reacts with Ru(bpy) 3 + to generate the excited state of Ru(bpy) 3 2+ with the overall effect of increasing the ECL signal up to 107%.…”
Section: Ecl Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent investigations of homogeneous oxidation of TPrA by a freely diffusing Ir complex demonstrated that this strategy can increase the ECL signal from a microbeads immunoassay, i.e., heterogeneous system by a “redox mediated” pathway (Fig. 6 ) [ 55 , 56 ]. The Ir(III) complex oxidized at the electrode to produce Ir(II) can oxidize the TPrA, which result in the formation of TPrA • , and in addition, it reacts with Ru(bpy) 3 + to generate the excited state of Ru(bpy) 3 2+ with the overall effect of increasing the ECL signal up to 107%.…”
Section: Ecl Systemsmentioning
confidence: 99%
“…The magnetic microbead is represented by the orange sphere while the [Ru(bpy) 3 ] 2+ luminophore and the [Ir(sppy) 3 ] 3− complex are labeled as Ru 2+ and Ir 3− , respectively. Adapted with permission from [ 56 ], Copyright (2024) Royal Society of Chemistry …”
Section: Ecl Systemsmentioning
confidence: 99%
“…[72] As shown by ECL microscopy of single beads, this approach resulted in a 70.9-fold enhancement of ECL in the bead-based assays upon applying a low potential of 0.9 V. Furthermore, investigation of the ECL reactivity in the presence of redox mediators helped define energetic criteria a mediator should fulfil to enhance the ECL emission, opening prospects for the rational design and synthesis of such mediators. [73] Another approach for enhancing ECL generation involves utilizing gold-coated [74] or carbon nanotubes (CNTs) modified [75] magnetic beads. The main idea was to extend the ECL emission further from the electrode surface by extending the electrode with conductive materials.…”
Section: Original Ecl Imaging Strategies For Enhanced Bioanalysismentioning
confidence: 99%
“…Electrochemiluminescence (ECL) has been widely used in the field of biological analysis and sensing due to its low background, high sensitivity, simple operation, and great controllability. , In recent years, for eliminating the interference of artificial or environmental factors and improving the accuracy and sensitivity of detection, more and more ratiometric ECL biosensors with dual emissions have been proposed and developed. For instance, Wang’s team developed PDI-CH 3 and g-C 3 N 4 , which emitted ECL at different potentials, and realized the ratio detection of carcinoembryonic antigen .…”
Section: Introductionmentioning
confidence: 99%